IAEA randomised trial of optimal single dose radiotherapy in the treatment of painful bone metastases. Issue 1 (July 2015) - Hoskin, Peter; Rojas, Ana; Fidarova, Elena; Jalali, Rakesh; Mena Merino, Ana; Poitevin, Adela; Oucrif, Seam; Abdelwahab, Sherif; Kochbati, Lotfi; Plieskiene, Aista; Casas, Francesc; Stojanovic, Susana; et al.
Abstract Background To determine the optimal single-dose radiotherapy schedule for pain from bone metastases in a multi-centre, international, randomised trial. Patients and methods 651 patients were randomised to either 8 Gy (n = 325) or 4 Gy (n = 326) radiotherapy. Pain at 4, 8, 12, 24 and 52 weeks was assessed using a Categorical Scale (CS) and a Visual Analogue Scale (VAS). The primary endpoint was response at 4 weeks. Results There was no significant difference in patient demographics and other co-variates. The complete response (CR) rate and ORR (complete or partial response) for all follow-up times were higher after 8 Gy (p = 0.02). The Kaplan–Meier actuarial rate (categorical scale) at 4 weeks for ORR was 80% after 8 Gy compared to 68% after 4 Gy (p = 0.0015). 117 re-treatments were given of which 72 were in the 4 Gy group and 45 in 8 Gy arm (p = 0.01). Conclusions There was a marked consistent difference in pain relief at all time points in favour of 8 Gy. These data reinforce the case for single dose 8 Gy radiotherapy to be recommended for metastatic bone pain in all healthcare settings.